Assessing emergency contraception awareness among married women in primary health centers within East Godavari villages: Research Article (Journal of Pharma Insights and Research, 2023)
This study aims to evaluate the awareness and comprehension of emergency contraception among adult married women attending Primary Health Centers (PHCs) in the villages of the East Godavari Region, Andhra Pradesh. A cross-sectional survey approach was employed, involving 386 married women aged 18 to 45. Exclusions comprised single women, those above 45, and those unwilling to participate. Multistage random sampling was utilized. Among the 386 participants, 53.5% were aged 30-40, with ages ranging from 23 to 44. Most had education up to the secondary level (53.7%). Approximately 57% were aware that unprotected intercourse could lead to unintended pregnancy. The mean knowledge score was 27.5%, with only 15.3% scoring above 60%. Age, number of offspring, education, employment, and monthly family income were significantly correlated with knowledge levels. Findings reveal limited awareness of emergency contraception, with higher knowledge among women aged 21-29 (31.5%), post-graduates (21.2%), employed individuals (19.5%), and families earning over 15,000 INR monthly (41.3%). Emphasizing education and promoting emergency contraception use is crucial based on our results.